Refugees, Asylum Seekers and Policy in Europe - Timothy J. Hatton; Jeffrey G. Williamson (Institute for the Study of Labor (IZA), 2004)
The number of refugees worldwide is now 12 million, up from 3 million in the early 1970s. And the number seeking asylum in the developed world increased tenfold, from about 50,000 per annum to half a million over the same period. Governments and international agencies have grappled with the twin problems of providing adequate humanitarian assistance in the Third World and avoiding floods of unwanted asylum seekers arriving on the doorsteps of the First World. This is an issue that is long on rhetoric, as newspaper reports testify, but surprisingly short on economic analysis. This paper draws on the recent literature, and ongoing research, to address a series of questions that are relevant to the debate. First, we examine the causes of refugee displacements and asylum flows, focusing on the effects of conflict, political upheaval and economic incentives to migrate. Second, we examine the evolution of policies towards asylum seekers and the effects of those policies, particularly in Europe. Finally, we ask whether greater international coordination could produce better outcomes for refugee-receiving countries and for the refugees themselves.
Keywords: F22; O19; J68; J61; 330; refugees; asylum seekers; asylum policy; international policy coordination; Flüchtlinge; Migrationspolitik; Asylrecht; EU-Staaten